Analisis Konflik Batin Tokoh Utama dalam Novel Hati Suhita Karya Khilma Anis: Prespektif Psikologi Karen Horney - Haniyah Kamilah Az-Zahra; Sugiarti Sugiarti (Universitas Palan, 2026)
This study aims to analyze the inner conflict experienced by the female protagonist, Alina Suhita, in the novel Hati Suhita by Khilma Anis using Karen Horney’s psychological perspective. The study is motivated by the complexity of the psychological struggles faced by the main character in dealing with marital pressures, family expectations, and socio-cultural demands within a pesantren environment. This research employed a descriptive qualitative approach using content analysis. The data source was the novel Hati Suhita by Khilma Anis, while the research data consisted of textual excerpts depicting the protagonist’s inner conflicts. Data were collected through reading and note-taking techniques and subsequently analyzed based on Karen Horney’s theory of neurotic tendencies. The findings reveal that Suhita’s inner conflict is influenced by marital pressures, family demands, social expectations, as well as cultural and religious values that shape her personality. These conflicts are manifested through three neurotic tendencies: moving toward people, moving against people, and moving away from people. The tendency of moving toward people is reflected in her obedience, self-sacrifice, and need for acceptance. The tendency of moving against people appears in her efforts to maintain self-respect, assertiveness, and courage in confronting pressure. Meanwhile, the tendency of moving away from people is shown through emotional withdrawal, solitude, and the pursuit of inner peace. The findings indicate that the protagonist’s inner conflict is dynamic and functions as a form of psychological adjustment to basic anxiety and socio-cultural pressures throughout the narrative.